ANALISIS BUSINESS MODEL CANVAS PADA SYAHIDA INN DALAM MENCARI ALTERNATIF STRATEGI BISNIS BADAN LAYANAN UMUM UIN SYARIF HIDAYATULLAH JAKARTA - Cahyadi, Ady; Salahuddin, Anwar (KEUNIS, 2022)
The development of the hotel sector in the pandemic covid-19 currently decrease so as prosecuting the business doers to survive and grow the business including Syahida Inn as a business units of Syarif Hidayatullah Jakarta The State Islamic University (UIN Jakarta). Therefore it is need of a business model exact to Syahida Inn knows how to run effectively, efficient, and economical. The purpose of this research is to develop the business model in the future. The kind of research is descriptive qualitative with bussiness model canvas (BMC) and strenght weakness opportunity threat (SWOT) approach. The result showed that the creation of value propositions in the future is sharia hotel, meeting room, wedding hall, cafe and restaurant with convenience, comfortable and hospitality in order will affect every element business model canvas there is an increase in the primary resource, owned the key activity, revenue streams, and increase the cooperation partners. The element of cost structure occured additional cost in promotion while on a customer segment focus to individual and government institutions. SWOT Analysis showed, Syahida Inn is in the first quadrant mean are in progressive strategy with the main focus on market penetration by increasing the promotion either online or offline, focus on market development with the introduction of products to the Tangerang Raya, Province of Banten and Province of Jakarta, and the latter focus on the product development by increasing the meeting facilities, wedding hall, cafe/restaurant, fitness center, and the auditorium/theatre room.